PEMANFAATAN SUMBER DAYA ALAM: PENDUKUNG AKTIVITAS BUDAYA MEGALITIK DI SITUS LOLAH, KECAMATAN TOMBARIRI, KABUPATEN MINAHASA, PROVINSI SULAWESI UTARA (THE EXPLOITATION OF NATURAL RESOURCES: THE SUBSISTENCE OF THE BEARERS OF THE MEGALITHIC CULTURE AT THE...) - Abdillah, Dariusman (Penerbit BRIN (BRIN Publishing), 2006)
ABSTRACT. The Exploitation of Natural Resources: The Subsistence of the Bearers of the Megalithic Culture at the site of Lolah, Minahasa Regency, North Sulawesi Province. Lolah sites is one of sites of exist in North Celebes which owning data from pickings of human life of past that is some waruga, menhir, dakon stones, ceramic fragments and also the swampy forest ceramic fragment around waruga. Arrange situation from this building megalithic do not refer into one certain pattern seen in distance of among waruga which is one with unequal other and disseminate. Substance artifact source petrify exist in this sites there are not far from location sites and in number which is a lot of even abundance. Rock used to menhir selected by a forms come near or as according to its allotment without change or form it totally. Substance from waruga of located in River Panaiki walls in west side of countryside Lemoh. Rock which is laid bare in the river Panaiki walls have equality with elementary substance of Waruga of exist in sites, beside that at the river is also met by the footstep existence of ex-base relief. Relied on the footstep hence can said that by this making waruga is conducted in place this substance source or rock reside in. After becoming grave form petrifies the desired is then brought to location sites. From result analyze physical which have been conducted can be said that by this election substance is relied on by its physical condition having high absorption, is easy to chiseled by because having hardness 2-3 Mosch scale. Even though the physical condition from this rock tuff, compact still and strong. From result of perception of geology known that by rocks of farm of Sites Lolah is congelation rock of young volcanic that is Pleistocene of early Holocene of Early Regional Morphology of sites and its surroundings represent a hilly with many rivers having the character of periodic, so that can be said that by accomplishment of adequate amount of water required here. That way also with level of fertility of land in this region is very conducive to make it as area plantation. Others the availability plant of elementary forest upon which inaker of wooden house very support for creation of settlement of resident in the region. In election of substance of maker of artifact stone, good that substance of maker of Waruga and also Menhir at past, have considered some aspect among other things is quality of substance as well as election of substance as according to its allotment.